Associations Between Income Status and Perceived Barriers to Using Long-Acting Reversible Contraception: An Exploratory Study - Henke, Leah; Martins, Summer; Boraas, Christy (Frontiers in Reproductive Health, 2022)
Introduction Barriers to long-acting reversible contraception (LARC) use in the United States have been described in prior studies, but few have focused on women's income status. We explored associations between income status and perceived LARC barriers in a community-based sample of reproductive-aged women. Methods Non-pregnant, heterosexually active women aged 18 to 40 years completed a cross-sectional survey at a large community event in the Midwestern U.S. in 2018. Outcome measures were comprised of 26 survey items gauging perceived barriers to LARC use (e.g., access barriers, side effects). We estimated crude and age-adjusted prevalence ratios (PRs) for each outcome by participants' income status: low-income (≤ 200% of federal poverty guideline) versus higher income. Results Low-income women (n = 72) were significantly more likely than higher income women (n = 183) to endorse 11 of the 26 barriers to LARC use (PR range, 1.23–7.63). Cost of LARC was the most frequently identified access barrier and was more acute for low-income women (PR 1.57, 95% CI 1.17–2.11). After adjustment for age, most associations were attenuated. However, low-income women were still more likely to report concerns about LARC use due to family expectations or beliefs (aPR 3.69, 95% CI 1.15–11.8). Conclusion Low-income women perceive more barriers to LARC access and more negative perceptions about use. While these associations also correlate with age, they nonetheless reflect concerns that impact contraceptive equity. Efforts to increase LARC access should address these barriers and focus on concerns more common among low-income women regarding LARC use.